Stable and Efficient Methylammonium‐, Cesium‐, and Bromide‐Free Perovskite Solar Cells by In‐Situ Interlayer Formation. (6th November 2020) - Wang, Minhuan; Tan, Shaun; Zhao, Yepin; Zhu, Pengchen; Yin, Yanfeng; Feng, Yulin; Huang, Tianyi; Xue, Jingjing; Wang, Rui; Han, Gill Sang; Jung, Hyun Suk; Bian, Jiming; et al.
Abstract: The vast majority of high‐performance perovskite solar cells (PSCs) are based on multi‐cation mixed‐anion compositions incorporating methylammonium (MA) and bromide (Br). Nevertheless, the thermal instability of MA and the tendency of mixed halide compositions to phase segregate limit the long‐term stability of PSCs. However, reports of MA‐free and/or Br‐free compositions are rare in the community since their performance is generally inferior. Here, a strategy is presented to achieve highly efficient and stable PSCs that are altogether cesium (Cs)‐free, MA‐free and Br‐free. An antisolvent quenching process is used to in‐situ deposit a polymeric interlayer to promote the growth of phase‐pure formamidinium lead tri‐iodide perovskite crystals with reduced defect density and to assist in photo‐excited charge extraction. The PSCs developed are among the best‐performing reported for such compositions. Moreover, the PSCs show superior stability under continuous exposure to both illumination and 85 °C heat. Abstract : An in‐situ formed polymeric interlayer enables enhanced photovoltaic performance of the methylammonium‐, cesium‐, and bromide‐free perovskite solar cells with superior photo‐ and thermal‐stability. The polymeric interlayer promotes growth of perovskite crystals with reduced defect density and improves the contact between the perovskite and hole transporting layers to assists in photo‐excited charge extraction.